Quality assurance systems of higher education - The case of european institutions: origin, evolution and trends - Ángela Corengia; Juan Carlos Del Bello; María Pita Carranza; Cecilia Adrogué (Revista Gestão Universitária na América Latina)
The purpose of this research is to analyze the origin, evolution, performance and trends of higher education quality assurance systems in the following European countries: Denmark, Norway, Sweden, Finland, Austria, Italy, Switzerland, Germany, Netherlands, United Kingdom and France. It also studies the performance and impact of the organizations that join the European Quality Assurance Agencies together. The main sources of data collection were in situ semi-structured interviews to members of these agencies. It was found that in higher education institutions there is a strong trend towards the development of ‘internal quality assurance systems' in response to the public policies known as 'quality audits'. This overview about what is taking place in Europe may provide innovative instruments that could be considered for higher education quality evaluation and accreditation in Latin-American countries: quality audits, disciplinary agencies, evaluation of the quality assurance agencies, among others.